(untitled) (International Seven Journal of Multidisciplinary, 2022)
In an era marked by global disruptions, climate risks, and rising ESG demands, strategic alliances with local suppliers have emerged as a key enabler of supply chain sustainability. This paper explores how localized partnerships enhance environmental, social, and operational performance by improving supply chain agility, reducing carbon emissions, and fostering community development. Drawing on academic literature and real-world examples, the study highlights the role of relational capital, regulatory alignment, and co-innovation in making these alliances effective. The findings suggest that engaging local suppliers is not only a risk mitigation strategy but also a pathway to achieving long-term resilience and contributing to global sustainability goals such as the United Nations Sustainable Development Goals (SDGs). The paper concludes with a call for further research on sector-specific and geopolitical variations in local sourcing strategies.